Does blue light affect sleep quality or performance? – empirical research based on anonymous surveys among medical students and physicians - Grużewska-Piotrowska, Kinga; Grużewska, Agnieszka; Pająk, Monika (Quality in Sport, 2023)
Introduction: Nowadays, more and more people use electronic devices. As the amount of time spent using them has increased, so has the quality of sleep. People go to bed later, and the process of falling asleep is delayed. In addition, sleep time is reduced, which translates into sleep deprivation. Many people think that blue light is only emitted from digital screens, but it is nothing new - it is part of the light emitted. Light is the most important factor regulating the circadian rhythms of the human body. All types of visible light can affect circadian rhythms, but blue light has the greatest impact. The aim of the study: The aim of the study was to assess if blue light affects sleep quality and performance by empirical research based on anonymous surveys among medical students and physicians. Materials and methods: The research material was collected using an anonymous online survey in May 2023. The obtained results were analyzed and verified on the basis of scientific literature and statistically processed using Microsoft Office Excel. Results: 92.3% of the respondents use electronic devices before going to bed, mostly the phone, and the time of using usually ranges from 30 minutes to 1 hour. Most of the people filling the questionnaire sleep on average 5-6 hours at night, of which as many as 81.7% declare that their sleep is not of good quality. 91.3% of respondents know what blue light is, but only 22.1% use protection against it before sleep. Conclusion: Exposure to blue light can affect sleep, performance and well-being. An important negative effect of exposure to blue light is a reduction in the quality and length of sleep, which can negatively affect performance. It is believed that in order to maintain a healthy circadian rhythm, it is necessary not only to increase the proportion of blue light in artificial light during the day, but also to reduce the amount of that light in the evening and night hours.